The Role of Noncommutative Quantum Gravity in Galactic Dynamics and Dark Matter Phenomena (Global Journal of Science Frontier Research, 2025)
This paper is based on the theory of noncommutative quantum gravity to interpret the observed gravitational effects caused by dark matter such as dark matter halos and the flatness of the rotation curves of galaxies In this work we explore whether noncommutative quantum gravity where spacetime coordinates follow a noncommutative algebra can naturally reproduce dark matter-like gravitational effects Our findings suggest that the self-interaction effects in noncommutative quantum gravity may provide an alternative explanation for dark matter-like gravitational effects potentially reducing the need for exotic matter